The acoustic oceanographic buoy. A light acoustic data acquisition system - Soares, C. (2014)
The Acoustic Oceanographic Buoy (AOB) is a light acoustic receiving device that incorporates acoustic and non-acoustic signals received in various channels along a vertical line array that provide oceanographic and environment measurements all of which are uniquely GPS time referenced. The physical characteristics of the AOB, in terms of size, weight and autonomy, will tend to those of a standard sonobuoy with, however, the capabilities: of local data storage, dedicated signal-processing, GPS self localizing, real-time monitoring and online data transmission.